European guidelines for prevention and management of influenza in hematopoietic stem cell transplantation and leukemia patients: summary of ECIL‐4 (2011), on behalf of ECIL, a joint venture of EBMT, EORTC, ICHS, and ELN. Issue 3 (31st January 2013) - Engelhard, D.; Mohty, B.; de la, R.; Cordonnier, C.; Ljungman, P.
Abstract Influenza may cause severe disease and mortality in leukemia patients and in hematopoietic stem cell transplantation recipients. The 4th European Conference of Infections in Leukemia (ECIL‐4) has developed evidence‐based guidelines for prevention and management of influenza infections in these patients. Real‐time reverse‐transcription polymerase chain reaction is the diagnostic test of choice, as it is the most sensitive and specific test for influenza. The risks for severe influenza and fatal outcome include lymphopenia, older age, influenza soon after transplantation or chemotherapy, steroid treatment, and lack of early antiviral therapy. Neuraminidase inhibitors (oral oseltamivir or inhalation of zanamivir) are currently the most effective therapeutic agents for influenza. Main preventive measures include annual vaccination of patients, household contacts, and hospital staff. This review summarizes ECIL‐4's main recommendations.